Additional postdilatation using noncompliant balloons after everolimus‐eluting stent implantation: Results of the PRESS trial. Issue 6 (16th March 2020) - Park, Gyung‐Min; Lee, Jae‐Hwan; Choi, Si Wan; Jeong, Jin‐Ok; Shin, Eun‐Seok; Bae, Jang‐Whan; Yoon, Hyuck‐Jun; Jung, Kyung Tae; Baek, Ju Yeol; Choi, Woong Gil; Choi, Rak Kyeong; Her, Sung‐Ho; et al.
Abstract: Background: There are limited data on the clinical value of routine postdilatation using noncompliant balloons after contemporary drug‐eluting stent implantation. Hypothesis: Additional postdilatation using noncompliant balloons after everolimus‐eluting stent implantation could provide better clinical outcomes. Methods: We randomly assigned 1774 patients with coronary artery disease to undergo additional high‐pressure postdilatation using noncompliant balloons and moderate‐pressure dilatation using stent balloons after everolimus‐eluting stent implantation. The primary endpoint was a composite of death, myocardial infarction (MI), stent thrombosis, and target vessel revascularization (TVR) 2 years after randomization. Results: The study was discontinued early owing to slow enrollment. In total, 810 patients (406 patients in the high pressure group and 404 in the moderate pressure group) were finally enrolled. At 2 years, the primary endpoint occurred in 3.6% of patients in the high pressure group and in 4.4% of those in the moderate pressure group ( P = .537). In addition, no significant differences were observed between the two groups in the occurrence of an individual end point of death (0.8% in the high pressure group vs 1.5% in the moderate group, P = .304), MI (0.2% vs 0.5%, P = .554), stent thrombosis (0% vs 0.2%, P = .316), or TVR (2.8% vs 2.6%, P = .880). Conclusions: The strategy of routine postdilatation using noncompliant balloons after everolimus‐eluting stent implantation did not provide incremental clinical benefits.